Effect of Cassava Peel Starch-Based Edible Coating with Galangal Extract Filtrate on Moisture Content, Weight Loss, and Vitamin C of Large Red Chili during Storage - Hasanah, Lutfiyatun; Hasdar, Muhammad; Fera, Melly; Deederm, Waroonporn (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
This study aimed to evaluate the effect of cassava peel starch-based edible coating enriched with galangal extract filtrate on the quality of large red chili peppers (Capsicum annuum L.) during storage. The experiment was conducted using a Completely Randomized Block Design (CRBD) with two treatment factors: galangal extract filtrate concentration (control, 5%, 10%, and 15%) and storage duration (5, 10, and 15 days). The observed parameters included moisture content, weight loss, and vitamin C content. Statistical analysis showed that both treatment and storage duration had significant effects (P<0.05) on all measured parameters. The best treatment was edible coating with 10% galangal extract filtrate (P2), which was able to maintain moisture content at 68.80%, reduce weight loss to 49.98%, and preserve vitamin C content at 2.18 mg/100g up to the 15th day of storage. This combination formed a semipermeable layer that effectively inhibited transpiration and slowed the degradation rate of nutritional compounds. These findings indicate that the incorporation of natural antimicrobial compounds from galangal extract filtrate into edible coatings can enhance the shelf life of large red chili peppers at room temperature. Keywords: cassava peel starch, edible coating, galangal filtrate, red chili, postharvest quality